Fungsi Afiks Infleksi Penada Pesona, Jumlah, dan Jender pada Verba Bahasa Arab: Tinjauan dari Perspektif Morfologi Infleksi dan Derivasi - Tajudin Nur (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This research analyzes the function of inflectional affixes as person, number, and gender in Arabic verbs from inflectional and derivational morphological perspectives. It is a qualitative research using structural linguistic method. Based on the data analysis, the result shows that there are two systems of inflection in Arabic verbs. They are inflectional suffix and inflectional prefix. The system of inflectional suffix occurs on perfect verbs (madi) and the system of inflectional prefix occurs on imperfect verbs (mudari'). The inflections function to mark the relation of verbs and their subjects in person, number, and gender in a sentence. The existence of inflection system proves that word-order in Arabic is flexible, i.e. the position of the verbs can be before or after the subjects. In addition to that, the system of inflection also shows that morphologically Arabic is inflectional, which means that its words are formed of morphemes. Each morpheme supports the concept different grammar.